A4_1 A Dish of Im-peck-able Taste - Wing, Matthew; Paton, Charlotte; Thomas, Kaia; McCabe, Nat (Physics Special Topics, 2021)
In this paper we aim to investigate the practicalities of being able to cook using sound waves. By assuming a spherical speaker surrounding a chicken of mass 1.50kg and a range of volumes (0dB-150dB), the time taken to cook the chicken was found within the range 1.4*10^{10} – 1.4*10^{-5} years. Additionally, by using this method it would cost 1.77 pence in order to cook the chicken. When compared to an average oven, this is 3.7% of the cost. Overall, despite the cheaper cost, cooking with sound would be impractical.